Traditional ecological knowledge in Georgia - Kikviże, Zaal, author.
1 online resource
Keywords: This multidisciplinary book develops a synthesis of traditional ecological knowledge in the Caucasus region in Georgia - a hotspot of natural and cultural diversity. Traditional ecological knowledge connects the knowledge of natural phenomena with the culture of a given human society, and Georgia is an excellent case study for observing this knowledge. The Caucasus region in particular is notable for its natural and ethnocultural diversity and this book weaves together the disciplines of history, environment and ethnography to develop a synthesis of traditional ecological knowledge. Tracing the history of Georgia through two main phases, the hunter and gatherer bands and the agrarian phase, the author examines important events such as the breeding of naked hexaploid wheat, the domestication of the grapevine and the development of viticulture. By utilising this historic perspective it allows us to clearly see how traditional ecological knowledge has increased in sophistication during the long prehistory of Georgia, and most importantly how this type of knowledge underpins the social and economic progress of traditional societies, not only in Georgia, but throughout the world. This book will be of great relevance to interdisciplinary-minded scholars and students who have an interest in the relationships between nature and human society, including anthropologists, historians, biologists, ecologists, botanists, sociologists and ethnographers.